Nanoparticles and the cardiovascular system: a critical review. (March 2013) - Donaldson, Ken; Duffin, Rodger; Langrish, Jeremy P; Miller, Mark R; Mills, Nicholas L; Poland, Craig A; Raftis, Jennifer; Shah, Anoop; Shaw, Catherine A; Newby, David E
Nanoparticles (NPs) are tiny particles with a diameter of less than 100 nm. Traffic exhaust is a major source of combustion-derived NPs (CDNPs), which represent a significant component in urban air pollution. Epidemiological, panel and controlled human chamber studies clearly demonstrate that exposure to CDNPs is associated with multiple adverse cardiovascular effects in both healthy individuals and those with pre-existing cardiovascular disease. NPs are also manufactured from a large range of materials for industrial use in a vast array of products including for use as novel imaging agents for medical use. There is currently little information available on the impacts of manufactured NPs in humans, but experimental studies demonstrate similarities to the detrimental cardiovascular actions of CDNPs. This review describes the evidence for these cardiovascular effects and attempts to resolve the paradox between the adverse effects of the unintentional exposure of CDNPs and the intentional delivery of manufactured NPs for medical purposes.